2004
DOI: 10.1073/pnas.0307415101
|View full text |Cite
|
Sign up to set email alerts
|

An efficient asymmetric synthesis of an estrogen receptor modulator by sulfoxide-directed borane reduction

Abstract: An efficient asymmetric synthesis of a selective estrogen receptor modulator (SERM) that has a dihydrobenzoxathiin core structure bearing two stereogenic centers is reported. The stereogenic centers were established by an unprecedented chiral sulfoxide-directed stereospecific reduction of an ␣,␤-unsaturated sulfoxide to the saturated sulfide in one step. Studies to elucidate the mechanism for this reduction are reported. Highly efficient Cu(I)-mediated ether formation was used to install the ether side chain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…The final step that involved cleavage of benzyl protecting group from the phenol turned out to be more challenging than we anticipated. 17 Our first attempts used hydrogenolysis with Pd/C, but this led to both debenzylation and an unexpected, undesired further reduction of the very hindered olefin in the oxabicyclic ring. An alternative debenzylation condition using FeCl 3 18 led to opening of the oxabicyclic ring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final step that involved cleavage of benzyl protecting group from the phenol turned out to be more challenging than we anticipated. 17 Our first attempts used hydrogenolysis with Pd/C, but this led to both debenzylation and an unexpected, undesired further reduction of the very hindered olefin in the oxabicyclic ring. An alternative debenzylation condition using FeCl 3 18 led to opening of the oxabicyclic ring.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative debenzylation condition using FeCl 3 18 led to opening of the oxabicyclic ring. However, a TMSI-mediated debenzylation, 17 conducted in the presence of thiourea, allowed us avoid any side reactions and obtain the desired free phenol derivative (Scheme 3). …”
Section: Resultsmentioning
confidence: 99%
“…A literature precedent, 36 in the context of a drug process development, has shown that a sulfoxide moiety can assist the reduction of an alkene otherwise sluggish towards borane reaction. We were glad to observe that addition of borane-dimethyl sulfide to hydroxyl sulfinyl ferrocene 4f provided compound 5f, with both desired reductions (Scheme 8).…”
Section: Methodsmentioning
confidence: 99%
“…In this case, however, stoichiometric quantities of the titanium reagent were required to achieve such high enantioselectivity. [58] In the field of biocatalysis very few sulfoxidation processes have been significantly scaled-up for the synthesis of biologically active compounds. Although several clear advantages have been already pointed out (vide supra), some key bottlenecks, such as inhibition of the enzyme activity by (high concentration of) both substrate and product, the low availability of catalyst and the downstream product recovery, due (in part) to the high dilution conditions have so far hampered the application of this methodology.…”
Section: Scheme 14mentioning
confidence: 99%